1997
DOI: 10.1103/physrevb.55.15706
|View full text |Cite
|
Sign up to set email alerts
|

Photon drag in single and multiple two-level quantum wells

Abstract: Starting from a density-matrix operator description we derive an expression for the photon-drag response tensor of a quantum-well system containing an arbitrary number of subbands. Subsequently we analyze the structure of the nonlinear response tensor and make a specialization to the case of a two-level quantum well. In the wake of a self-consistent calculation of the local fields in a two-level well and in multiple quantum wells the photon-drag currents are determined. We illustrate the main ingredients of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…It is found from Fig. 2 that, without external bias applied, with an increase of the incoming frequency the drag current undergoes a change from negative to positive (so-called polarity of the photon drag in quantum well structures), and the zero crossing is at $1X13w 21 , which is blue shifted from the electronic resonance at w 21 due to the local-field effects [16]. Also the spectrum shows that the two peaks are quite broadened.…”
Section: Numerical Results and Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…It is found from Fig. 2 that, without external bias applied, with an increase of the incoming frequency the drag current undergoes a change from negative to positive (so-called polarity of the photon drag in quantum well structures), and the zero crossing is at $1X13w 21 , which is blue shifted from the electronic resonance at w 21 due to the local-field effects [16]. Also the spectrum shows that the two peaks are quite broadened.…”
Section: Numerical Results and Discussionmentioning
confidence: 93%
“…At the applied field of 1.0 V/mm the amplitudes of the two peaks are increased, again the zero crossing point is moved upwards in frequency, which implies that the local-field shift becomes more important with reducing the energy separation. From the previous study [16] it has been shown that the antisymmetric shape of the photon drag response tensor, characterized by H 12 H 21 À , is not affected with the change of external field strength, and since the relaxation energy is fixed, the amplitude of the response tensor is unchanged, too. Thus, the variation of the photon drag current shows the change of the internal dynamics, which manifests itself via g * x g z .…”
Section: Numerical Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our recent studies on quantum-well systems, it has been found that localfield effects play an important role in determining the linear absorption peak location [20], the shape of absorption spectrum [21], and nonlinear response, such as photondrag current [22] and second harmomic generation [23]. In this paper starting with an integral equation derived from the Maxwell-Lorentz equations, the expressions of the field in each layer are given.…”
Section: Introductionmentioning
confidence: 99%